Quetiapine and novel PDE10A inhibitors potentiate the anti-BuChE activity of donepezil - Joanna Sikora; Maria Podsiedlik; Tadeusz Pietras; Marcin Kosmalski; Mikołaj Matłoka; Rafał Moszczyński-Petkowski; Maciej Wieczorek; Magdalena Markowicz-Piasecka (Taylor & Francis Group, 2020)
The symptoms of Alzheimer's disease (AD) do not include only memory loss and cognitive decline but also neuropsychiatric manifestation. These AD-related symptoms are usually treated with the aid of antipsychotics; however, their effects on cognition and safety remain unexplored. The present study determines the effects of quetiapine, an atypical antipsychotic, and two imidazo[1,2-a]pyrimidine-based inhibitors of PDE10A on the activity of human cholinesterases. Quetiapine moderately inhibited BuChE (IC50 = 6.08 ± 1.64 µmol/L) but improved the anti-BuChE properties of donepezil by decreasing its IC50 value. Both PDE10A inhibitors were found to possess moderate anti-AChE properties. The combined mixtures of donepezil and imidazo[1,2-a]pyrimidine analogues produce a synergistic anti-BuChE effect which was greater than either compound alone, improving the IC50 value by approximately six times. These favourable interactions between quetiapine, PDE10A inhibitors and clinically approved donepezil, resulting in improved anti-BuChE activity, can lead to a wider variety of potent AD treatment options.